Cover Picture: Dual Gold‐Catalyzed Cycloaromatization of Unconjugated (E)‐Enediynes (Angew. Chem. Int. Ed. 7/2019). Issue 7 (21st December 2018) - Zamani, Farzad; Babaahmadi, Rasool; Yates, Brian F.; Gardiner, Michael G.; Ariafard, Alireza; Pyne, Stephen G.; Hyland, Christopher J. T.
Abstract : Dual gold activation is an important catalytic mode in homogeneous catalysis. In their Communication onpage 2114 ff., S. G. Pyne, C. J. T. Hyland, and co‐workers report that ( E )‐enediynes undergo a dual gold‐catalyzed cycloaromatization towards isoindolinones. They use electronic differentiation of triple bonds to direct the formation of a propiolic gold acetylide, represented as a gold‐coveting dragon, which then reacts with a π‐coordinated enyne moiety, illustrated by Rumpelstilzchen spinning his golden thread.